Mental health in the Austrian general population during COVID-19: Cross-sectional study on the association with sociodemographic factors - Humer, Elke; Schaffler, Yvonne; Jesser, Andrea; Probst, Thomas; Pieh, Christoph (Frontiers in Psychiatry, 2022)
The impact of the Coronavirus disease (COVID-19) pandemic and the associated governmental restrictions on mental health have been reported for different countries. This study evaluated mental health two years after the emergence of COVID-19 in Austria and the association with socio-demographic factors (i.e., age, gender, education, income, employment status, partnership status, migration background). A representative sample (N = 1,031) of the Austrian general population was surveyed online end of April 2022. Indicators of mental health were depression (PHQ-9), anxiety (GAD-7), insomnia (ISI), alcohol abuse (CAGE), eating disorders (SCOFF), and stress (PSS-10). 1,031 participants filled out the online survey (50.3% women; mean age: 45.6 ± 17.23 years). Cut-offs for clinically relevant depression were exceeded by 28%. 16% scored above the cut-off for clinically relevant anxiety symptoms, 15% above the cut-off for clinical insomnia, 18% above the cut-off for alcohol abuse, 26% above the cut-off for eating disorders (SCOFF) and 65% above the cut-off for moderate to high stress. Comparisons with a representative Austrian sample recruited during the first weeks of the COVID-19 pandemic in Austria (April 2020) revealed increases in depression (from 21% to 28%) but no significant changes in anxiety, insomnia, and moderate to high stress. Multivariable logistic regression showed the strongest associations of mental health indicators with age, income, and gender. Increasing age and income were associated with lower odds for mental health symptoms. Being female compared to male increased the odds of depressive symptoms while decreasing the odds of alcohol abuse. The COVID-19 crisis seems particularly stressful for younger adults (<35 years) and people with low income (<€2,000 net household income per month). Policymakers need to consider optimal intervention methods for mental disorders among young and low-income individuals.